USING PEDOMETERS IN ELEMENTARY PHYSICAL EDUCATION - Bülent Agbuga (Pamukkale University, 2010)
Identifying children's physical activity level can provide valuable information to change their lifestyles positively. Such inquiry may encourage people to be more physically active although physical activity is not only one factor to deal with health-related problems such as obesity. Such inquiry may also provide important implications for teachers who want to design physical activity programs where students' physical activity maximized. The purposes of this article are (1) to give a very brief information about physical activity/inactivity and pedometers, (2) to explain the importance of using pedometers in physical education classes, and, (3) to indicate important contributions of pedometer-based physical education.